Community Implementation of a Prehospital Spinal Immobilization Guideline. (1st November 2016) - Jones Rhodes, Whitney; Steinbruner, David; Finck, Lani; Flarity, Kathleen
Abstract: Objective: The purpose of this study was to qualitatively describe the underpinnings of the successful implementation of a collaborative prehospital spinal immobilization guideline throughout the emergency medical services (EMS) community in two counties in Colorado. We also describe lessons learned that may be beneficial to other communities considering similar initiatives.Methods: Qualitative data were collected from key informants who were directly involved in the implementation of a new prehospital spinal immobilization guideline among four community hospitals in two different hospital systems and the associated EMS providers within the two counties. We interviewed a purposively selected sample of emergency department (ED) physicians and other ED staff, hospital decision makers, EMS educators as well as fire department and EMS medical directors. Data were collected and reviewed until saturation was achieved. We conducted qualitative analysis to summarize and synthesize themes.Results: Ten key informants were interviewed, at which point saturation was achieved and several clear themes emerged. Participants described successful community-wide guideline implementation despite a history of competition, isolation, and conflict between the various EMS organizations and hospitals on past EMS and trauma initiatives. Factors related to success included the nearly universal perception that the initiative was "cutting edge" and thus an important paradigm shift in care for the community, as a whole. Participants reported the ability of community stakeholders to jointly assure a collaborative approach, characterized by intensive education for EMS personnel and others involved, and the ability of the community to together secure the new equipment required for success.Conclusions: Key informants described a convergence of factors as leading to the successful implementation of a prehospital spinal immobilization guideline. Lessons learned regarding how to overcome a tradition of competition and isolation to allow for success may be useful to other communities considering similar initiatives.